HASIL BELAJAR KOGNITIF IPA FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DENGAN PERMAINAN BALON-BALON PINTAR PADA SISWA KELAS IX SMP NEGERI 3 TAMBANG - Yesi Malinda; Azizahwati Azizahwati; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to determine the increase in physics learning outcomes class IX SMP N 3 Tambang using model cooperative learning type group investigation (GI) with smart ballons game. The form of this study was Quasi Experimental Design with design Posttest-Only Control Design. The sample of research is student of IX.3 as experiment class and IX.2 as control class. Instrument of data collection is the result of cognitive learning given to the post learning sample. Data analysis techniques used are descriptive and inferential analysis. The results showed the students average absorption by applying model cooperative learning type GI with smart ballons game is higher than the application of conventional learning. Thus concluded that the application of learning model cooperative learning type GI with smart ballons game can improve student learning outcomes in learning Physics in dynamic electricity material in class IX SMP N 3 Tambang.Keywords: Model Cooperative Learning Type GI With Smart Ballons Game, LearningOutcomes.